40Ar-39Ar Age Studies of Four Yamato-74 Meteorites - Kaneoka, Ichiro; Ozima, Minoru; Yanagisawa, Masahisa (1979)
P(論文) ^<40>(Ar)-^<39>(Ar) ages have been obtained for four Yamato-74 meteorites (Yamato-74640,-74190,-74159 and -74097) from Antarctica. Yamato-74640 (H5-6) shows a plateau age of 4407±71 m.y. (1σ) at higher temperatures. This age probably corresponds to the time of formation or a very intense metamorphism for this meteorite. Yamato-74190 (L6) indicates a ^<40>(Ar)-^<89>(Ar) age spectrum with a low temperature plateau-like age of 357±32 m.y. The apparent ^<40>(Ar)-^<39>(Ar) age increases up to about 1300 m.y., but does not reach a high temperature plateau. The apparent young age would reflect the time of degassing due to the collisional process of the parent body, which has been observed in many L-chondrites. Yamato-74159,which is a eucritic polymict breccia, has a similar age spectrum to that of Pasamonte obtained by PODOSEK and HUNEKE (Geochim. Cosmochim. Acta, 37,667,1973), indicating a plateau age of 4075±49 m.y. at intermediate temperatures (850-1250℃). This age may reflect the time of the later degassing event such as the impact of meteoroids on the parent body of the eucrite. Yamato-74097 (Diogenite) seems to show a relatively young ^<40>(Ar)-^<39>(Ar) age of about 1100 m.y., though the uncertainty in the obtained age is larger for this diogenite than those for the other samples due to its low K-content. From both the value of the age and the age spectrum, this diogenite seems to have a different history from those of ordinary chondrites and achondrites known to date. departmental bulletin paper